Integration of Islamic Education and Economic Empowerment in Islamic Organizations' SDG-Based Da'wah Programs - Suparmin; Abdul Hamid; Badrah Uyuni; Hafiz Shuaib Farooq (Institut Agama Islam An-Nawawi Purworejo, 2025)
This integration is based on the principles of independence, brotherhood, and welfare, which are the main foundations of Islamic education. This study aims to explain how the integration of Islamic education and economic empowerment is implemented in the da'wah program run by the Islamic organization Nahdlatul Ulama (NU) Jati Sampurna Bekasi Branch, oriented towards sustainable development goals (SDGs). In its implementation, da'wah is not only directed at strengthening religious values through religious study groups, regular religious studies, and moral development, but is also synergized with programs to improve the economic welfare of the community. This study uses a qualitative approach with descriptive methods. Data were obtained through observations of da'wah and empowerment activities and interviews with NU Jati Sampurna Branch administrators, community leaders, and program participants. The results show that this empowerment-based da'wah model is able to strengthen religiosity while encouraging increased economic capacity of the community, in line with SDG targets such as poverty alleviation, improving the quality of education, and community-based inclusive economic development.